Beyond transplantation and hybridisation: the distinctiveness of the System of Case Guiding. (2nd January 2022) - Sze Kiun, Joshua Fung
ABSTRACT: Two paradigms are dominant in the international discourse on the System of Case Guiding ('SCG'). The first 'transplantation' paradigm posits that the SCG is a straightforward transplant of the Anglo-American system of common law. The second 'hybridisation' paradigm views the SCG as a distinct but inferior common law, held back by its 'Chinese characteristics'. These paradigms are challenged as being partial, outdated and inaccurate accounts of the SCG on two tiers. On a comparative and theoretical tier, this article builds upon the foundations of three concepts to mount its sustained critique. First, preferring Teubner's description of legal change and reform as proceeding by legal 'irritation', it is argued that the notion of 'transplantation' is too blunt an account of how contemporary legal reform within the People's Republic of China ('PRC') has sought to learn from and build upon the experiences of other legal systems. Second, accepting Santos's call for a decentred approach to globalisation, the development of the SCG is situated foremost within its local context, instead of by reference to foreign systems of precedent. In doing so, this article moves beyond the old paradigms of 'transplantation' and 'hybridisation' towards a recognition of the distinctiveness of the SCG as an autochthonous innovation of the Chinese legal community that has been precisely tailored to its unique conditions. Third and finally, applying the concept of legal plurality to the practice of using Guiding Cases and precedent more generally, it is recognised that the development of the SCG has been driven, not only by the top-down actions of the Supreme People's Court ('SPC'), but also by its synergistic interaction with the bottom-up use of precedent by the wider legal community of litigants and legal professionals. Freed from the conceptual burdens of these two paradigms, this article proceeds to advance this theoretical basis for understanding the SCG by reference to an empirical analysis of three Guiding Cases – Numbers 24, 15 and 9 . The first two are the most highly cited Guiding Cases; the third was one of the most often cited Guiding Cases as well, before losing its guiding effect. By reference to these three case studies, which involved analysing 939 judicial decisions, this article constructs a pluralistic account of the evolving judicial practice of referencing Guiding Cases. First, it is found that the distinctiveness of the SCG stems from the referent function of Guiding Cases, which is at the core of its judicial practice. This referent function is evident from the vast majority of judicial decisions that cite or refer to one of the three Guiding Cases as a formal authority for reaching their conclusion, without more. Second, however, it is also found that while this function of Guiding Cases might be the dominant form of judicial practice at this moment, this practice is not monolithic and is in fact changing at the margins. A small minority of cases since 2016 are illustrative of the potential trajectories of evolution for the next ten years of the SCG and the judicial practice of referencing Guiding Cases. These cases have evinced a greater willingness by courts to engage more meaningfully with precedent-based forms of reasoning, such as arguing from the facts of a case and arguing from the principles stated therein. This greater engagement has not only been driven by top-down mandates to search for and reference a wider variety of cases beyond Guiding Cases, but has also been driven by the bottom-up use of precedents by litigants in presenting their legal arguments before the courts. While these marginal practices are still in their infancy, the empirical analysis provides evidence of a complex, complicated and pluralistic practice of greater and more substantial reliance on Guiding Cases within the PRC.